2020
DOI: 10.1016/j.quascirev.2019.106136
|View full text |Cite
|
Sign up to set email alerts
|

Linking Danube River activity to Alpine Ice-Sheet fluctuations during the last glacial (ca. 33–17 ka BP): Insights into the continental signature of Heinrich Stadials

Abstract: Please note that this is an author-produced PDF of an article accepted for publication following peer review. The definitive publisher-authenticated version is available on the publisher Web site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 182 publications
0
21
0
Order By: Relevance
“…In three MeBo drilling sites, Riedel et al (2020) describe “sand layers several millimeters in thickness” as “typical” in the deeper units, between 45 and 140 mbsf. The analysis of long‐piston cores also shows the presence of sandy layers of thickness increasing with depth (Martinez‐Lamas et al, 2020). These observations indicate the presence of higher permeability layers within the overall fine grained sediments of the area.…”
Section: Discussionmentioning
confidence: 99%
“…In three MeBo drilling sites, Riedel et al (2020) describe “sand layers several millimeters in thickness” as “typical” in the deeper units, between 45 and 140 mbsf. The analysis of long‐piston cores also shows the presence of sandy layers of thickness increasing with depth (Martinez‐Lamas et al, 2020). These observations indicate the presence of higher permeability layers within the overall fine grained sediments of the area.…”
Section: Discussionmentioning
confidence: 99%
“…17.2-15.7 ka BP, hyperpycnal floods from the Danube River were identified as the main sediment source, and sediment deposition and burial of reactive minerals under lacustrine oxic bottom water conditions was much more rapid than modern sedimentation. The analysis of clay mineralogy and Nd isotope signatures of the Danube and its main tributaries suggested that early periods of meltwater release during 32.5-30.5 ka BP supplied smectite-poor, chlorite and dolomite-rich sediments from Eastern Alpine domains (Martinez-Lamas et al, 2020). Thereafter between 30 and 29 ka J o u r n a l P r e -p r o o f…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The Danube River is considered to be the major source of sediment to the north-western margin of the Black Sea (Lericolais et al, 2013), especially during the ca. 32-17 ka period (Martinez-Lamas et al, 2020). Over this period, the river was characterized by high flood activity supplying huge amounts of sediment to the margin and the deep basin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If this change in strength arose from altered density of outflowing Mediterranean Water, in a manner similar to velocity minima during sapropels, this would require a large freshwater discharge into the Mediterranean during H1.1. In principle, this could have come from the Fennoscandian ice sheets via the Caspian‐Black Sea corridor (Bahr et al, 2005; Denton et al, 1999; Major et al, 2002, 2006; Martinez‐Lamas et al, 2020; Ryan et al, 2003; Soulet et al, 2013; Tudryn et al, 2016) or from the Alps (Braakhekke et al, 2020; Monegato et al, 2017; Ravazzi et al, 2014; Tombo et al, 2015). However, within radiocarbon dating uncertainties, the timing and pattern of freshwater discharge to the Mediterranean reported by these authors does not fit with the MOW weakening events observed in this study.…”
Section: Impact Of Surface and Intermediate Water Circulation On The mentioning
confidence: 99%